The Impact of Inheritance and Gift Tax on the Formation of Local Government Revenue with Selected Local Governments as an Example - Królak, Daria (Journal of Finance and Financial Law, 2014)
The purpose of this article is to examine how strong impact on local government revenues has an inheritance and gift tax. The author presents three different classifications of local government revenues: statutory and two classifications taken from Beata Guziejewska’s and Krystyna Piotrowska-Marczak’s books. The analysis shows that the inheritance and gift tax, mentioned in the statutory division as a local government income, has a marginal impact on revenue’s formation. However, in the case of book definitions, an author excludes the tax from local government revenues, making it a foreign income and depriving it of any influence on the formation of local government income.